Electron spin interactions in chemistry and biology : fundamentals, methods, reactions mechanisms, magnetic phenomena, structure investigation /: fundamentals, methods, reactions mechanisms, magnetic phenomena, structure investigation. (2016) - Likhtenshteĭn, G. I (Gert︠s︡ Ilʹich)
No abstract available